Variation in the human Achilles tendon moment arm during walking. Issue 2 (25th January 2017) - Rasske, Kristen; Thelen, Darryl G.; Franz, Jason R.
Abstract: The Achilles tendon (AT) moment arm is an important determinant of ankle moment and power generation during locomotion. Load and depth-dependent variations in the AT moment arm are generally not considered, but may be relevant given the complex triceps surae architecture. We coupled motion analysis and ultrasound imaging to characterize AT moment arms during walking in 10 subjects. Muscle loading during push-off amplified the AT moment arm by 10% relative to heel strike. AT moment arms also varied by 14% over the tendon thickness. In walking, AT moment arms are not strictly dependent on kinematics, but exhibit important load and spatial dependencies.